Typhoid and Scrub Typhus Coinfection in a Returned Traveler - Christopher Wen-Xing Seow MBBS; Veena Logarajah MB ChB, MRCPCH; Natalie Woon Hui Tan MBBS, MRCPCH (SAGE Publishing, 2017)
This is a case report of a 12-year-old returned traveler with typhoid and scrub typhus coinfection. The diagnosis of typhoid was made early with blood cultures and Widal Weil Felix serology. Persistent fever despite appropriate antibiotics for typhoid fever prompted a search for concomitant infection, which led to the diagnosis of scrub typhus confirmed by Orientia tsutsugamushi serology. The patient was given doxycycline with good clinical response. Scrub typhus infection should be an early consideration in the differential diagnoses of fever in a returned traveler from regions where it is endemic. Coinfections should be taken into consideration particularly when fever or symptoms persist despite adequate therapy for a previously identified microorganism.